Electronic structure of metal oxide dications with ammonia ligands and their reactivity towards the selective conversion of methane to methanol - Claveau, Emily E.; Miliordos, Evangelos (Frontiers in Chemistry, 2024)
High-level quantum chemical calculations are performed for the (NH3)MO2+ and (NH3)5MO2+ species (M = Ti-Cu), extending our previous work on the bare MO2+ ions. The potential energy curves along the M-O distance are constructed for the ground and multiple excited electronic states of (NH3)MO2+ and are compared to those of MO2+. We see that ammonia stabilizes the oxo states (M4+O2−) over the oxyl (M3+O⋅−) ones. This trend is intensified in the (NH3)5MO2+ species. We then examined the reaction of the latter species with both methane and methanol. We find that the oxyl states activate a C-H bond easily with barriers smaller than 10 kcal/mol across all first-row transition metals, while the barriers for the oxo states start from about 50 kcal/mol for M = Ti and decrease linearly to 10 kcal/mol going toward M = Ni. This is attributed to the increasing spin density on the oxygen atom observed for the oxo states. The most important finding is that the formation of hydrogen bonds between the OH group of methanol and the N-H bonds of the ammonia ligands increases the activation barriers for methanol considerably, making them comparable to and slightly higher than those of methane. This finding suggests a new strategy to slow the oxidation of methanol, leading to the long-desired higher methane-to-methanol selectivity.